2023
DOI: 10.1186/s13756-023-01227-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental contamination across multiple hospital departments with multidrug-resistant bacteria pose an elevated risk of healthcare-associated infections in Kenyan hospitals

Abstract: Background Healthcare-associated infections (HAIs) are often caused by multidrug-resistant (MDR) bacteria contaminating hospital environments which can cause outbreaks as well as sporadic transmission. Methods This study systematically sampled and utilized standard bacteriological culture methods to determine the numbers and types of MDR Enterococcus faecalis/faecium, Staphylococcus aureus, Klebsiella pneumoniae, Acinetobacter baumannii, Pseudomona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Therefore, there was no direct evidence to indicate whether the origins of the relevant strains in pregnant women were from the hospital, the community environment, or other transmission chains, particularly the newly created CTs isolates. Despite these limitations, the findings in the present study are significant since, in the potential chain of mother-to-newborn transmission, all are very susceptible to infections, with quite limited antibiotics for therapeutic options, particularly in the face of previous fatal neonatal outbreaks and contamination over animate and inanimate environment ( Osei Sekyere et al, 2021 ; Odoyo et al, 2023 ; Woon et al, 2023 ). In China and most developing countries, there needs to be more individual rooms to take contact precautions and enforce patient isolation in the Department of Obstetrics and Gynecology, especially in public hospitals, which is an issue that deserves more attention.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, there was no direct evidence to indicate whether the origins of the relevant strains in pregnant women were from the hospital, the community environment, or other transmission chains, particularly the newly created CTs isolates. Despite these limitations, the findings in the present study are significant since, in the potential chain of mother-to-newborn transmission, all are very susceptible to infections, with quite limited antibiotics for therapeutic options, particularly in the face of previous fatal neonatal outbreaks and contamination over animate and inanimate environment ( Osei Sekyere et al, 2021 ; Odoyo et al, 2023 ; Woon et al, 2023 ). In China and most developing countries, there needs to be more individual rooms to take contact precautions and enforce patient isolation in the Department of Obstetrics and Gynecology, especially in public hospitals, which is an issue that deserves more attention.…”
Section: Discussionmentioning
confidence: 89%
“…Pregnant women who undergo physiological immunological changes, present a notable risk group for acquiring or reactivating infections ( Hazenberg et al, 2021 ; Osei Sekyere et al, 2021 ), and who are carriers of AB are not only more predisposed to associated infections at an uncertain time during pregnancy, intrapartum or postpartum period, but also have a risk of maternal carriers transferring the AB to their newborns ( Sood et al, 2019 ; Osei Sekyere et al, 2021 ). AB as a cause of pneumonia, urinary tract infections, and sepsis ( Cavallo et al, 2023 ), has manifested among pregnant women and newborns in numerous countries ( Sood et al, 2019 ; Osei Sekyere et al, 2021 ; Ghanchi et al, 2023 ; Odoyo et al, 2023 ; Woon et al, 2023 ), inciting adverse outcomes including spontaneous abortion, premature labor, and perinatal deaths ( Aivazova et al, 2010 ; He et al, 2013 ; Osei Sekyere et al, 2021 ). Although the World Health Organization (WHO) estimates that puerperal sepsis accounts for 10.68% of maternal deaths, antepartum screening for AB remains scant, with prevailing data often emerging from retrospective studies and postpartum examinations ( Say et al, 2014 ; Bebell et al, 2017 ; Osei Sekyere et al, 2021 ; Sousa et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, Enterobacteriaceae isolates showed third-generation cephalosporins (3GCs) resistance, ranging from 50 to 100%. Third-generation cephalosporins-resistant Enterobacteriaceae (3GCRE), including Escherichia coli, Klebsiella pneumoniae, and Enterobacter cloacae , were recently reported in Kenya among severely ill COVID-19 patients [ 13 ], from ‘high-touch’ sites in multiple hospital departments [ 42 ], and in communities and hospitals settings [ 43 ]. These bugs appear among the top World Health Organization (WHO) global priority pathogens (GPP), along with carbapenem-resistant- Enterobacteriaceae , - Pseudomonas, and -Acinetobacter baumannii , categorized as critical due to drug resistance and the need to discovery and development of new antimicrobial agents [ 44 ], In Enterobacterales , 3GC resistance is predominantly due to the production of extended-spectrum β-lactamases (ESBL) [ 45 ] and 3GCRE-strains pose higher disease burden than carbapenem-resistant ones [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Many of the most relevant pathogens associated with HCAIs (methicillin-resistant Staphylococcus aureus, vancomycin-resistant enterococci, Acinetobacter baumannii, Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Enterobacter species, and Clostridioides difficile) can be shed from infected or colonized patients and survive on environmental surfaces for extended periods, some for several months. [3][4][5][6][7][8][9][10][11][12][13] Environmental surfaces associated with the transmission of HCAIs include walls, 8,14 fabrics and plastics, 15 furniture, 16 hospital bed handsets and bedrails, 10,17 and soap dispensers. [18][19][20] Many studies underappreciate the significance of the bedframe or mattress deck as a potential source of bacteria leading to HCAIs.…”
Section: Introductionmentioning
confidence: 99%